Food Preference of Semi-Provisioned Macaques Based on Feeding Duration and Foraging Party Size - ISLAMUL HADI; BAMBANG SURYOBROTO; DYAH PERWITASARI- FARAJALLAH (Bogor Agricultural University, Indonesia, 2007)
The long-tailed macaques (Macaca fascicularis; also called crab-eating monkeys) have broad geographic distribution in continent and archipelago of Southeast Asia. They have wide ecological plasticity to adapt to various environments. Due to disturbance of habitat and intensive contact with human, long-tailed macaques change their feeding behavior. Here we present food preferences of long-tailed macaques that live in Cikakak Monkey Park in Central Java. By recording the number of individuals who fed on a food patch and the duration of eating the food, we found that proportion of their food from natural resources is greater than those from human sources. They shifted to omnivory feeding mode to adapt to the changing environment. At many times, this omnivorous feeding brought forth crop-raiding which were not in natural behavioral repertory. Conservation effort of long-tailed macaques, and primate in general, should consider the aspect of human-modulated behavior in feeding ecology if we wish to be successful. Key words: feeding ecology, long-tailed macaques, Cikakak monkey park, party size, feeding duration, omnivorous